Late, But Not Too Late? Postponement of First Birth Among Highly Educated US Women - Natalie Nitsche; Hannah Brückner (European Journal of Population, 2020)
We examine the link between the postponement of parenthood and fertility outcomes among highly educated women in the USA born in 1920–1986, using data from the CPS June Supplement 1979–2016. We argue that the postponement–low fertility nexus noted in demographic and biomedical research is especially relevant for women who pursue postgraduate education because of the potential overlap of education completion, early career stages, and family formation. The results show that women with postgraduate education differ from women with college education in terms of the timing of the first birth, childlessness, and completed fertility. While the postponement trend, which began with the cohorts born in the 1940s, has continued among highly educated women in the USA, its associations with childlessness and completed parity have changed considerably over subsequent cohorts. We delineate five distinct postponement phases over the 80-year observation window, consistent with variation over time in the prevalence of strategies for combining tertiary education and employment with family formation.
Keywords: 300; Fertility; Education; College; Childlessness; Postponement; First birth; Postgraduate; United States